Leiomyoma of the vulva: a diagnostic challenge - Saxena, Shilpi; Goel, Suyash; Sen, Alok D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Smooth muscle tumours of vulva are rare and therefore can be missed clinically. Our patient, 48-year-old lady presented with lump in the left vulva that was clinically diagnosed as Bartholin duct cyst. The lumpectomy was done under local anaesthesia and the lesion was sent for pathological examination. On gross examination the mass was 3.5 cm in diameter. The microscopic examination revealed the lump to be leiomyoma and no necrosis or atypia was present. The final diagnosis of “vulval leiomyoma” was given. Postoperative period was uneventful, and the patient is on regular follow up and there has been no recurrence. Leiomyoma should be kept as a differential diagnosis when a lady presents in late reproductive age group with unilateral swelling in vulvar region which is firm in consistency and the lump must be sent for histopathological examination for definitive diagnosis and rule out malignancy. The pathologists play a critical role in recognition and management of smooth muscle tumors of the vulva and to rule out leiomyosarcoma.